The Prevalence of Dyslipidemia in Pediatric Obesity and its relation to Life Style of Obese Children: Prevalensi Dislipidemia pada Obesitas Anak dan Hubungannya dengan Gaya Hidup Anak Obesitas - Altaan, Esraa Azzam; Alsarraf, Zahraa; Abow, Frdoos Hameed (Indonesian Journal on Health Science and Medicine, 2025)
Background: Pediatric overweight contributes to adulthood obesity, leading to increased mortality and morbidity. There are a number of environmental and genetic factors that can have an effect on one's weight, including nutrition and physical activity. It is important to note that the prevalence of dyslipidemia in children and adolescents serves as a warning signal at both the individual and population levels. This is because having an excessive amount of body weight might lead to health concerns associated with dyslipidemia. Aim: To evaluate the prevalence of dyslipidemia and the relationship between metabolic health and dietary and physical activity habits in obese children and adolescents. Methodology: A cross-sectional and case control study was conducted on 62 children aged 4-14 years at Ibn-Sena Taching Hospital and and Alwafaa center for endocrine and diabetes mellitus from 1st February 2024 to 1st November 2024. The sample consisted of 22 obese children and 40 normal weight children without dyslipidemia. Data was collected through questionnaires, height, weight, BMI, waist circumference, and blood samples. Independent t-test and Fisher Exact test. Results: The study revealed that obese children have a mean age of 10.97 years, higher cholesterol, triglyceride, and LDL levels, and lower HDL levels. Only 4 of these children with higher waist circumference and BMI had dyslipidemia, a prevalence of 18.2%. These children had a family history of obesity. Playing video game was 75.0% in dyslipidemic obese children, and no significant differences was found in snacks. Conclusion: Children with a BMI over normal were frequently affected by dyslipidemia. Children with dyslipidemia were older and had elevated fundamental anthropometric measurements, such as waist circumference and BMI, compared to overweight and obese children without lipid abnormalities. Highlights: ediatric obesity links to adult dyslipidemia, morbidity, and genetic factors. Cross-sectional study of 62 children; BMI, waist, and lipid tests. Dyslipidemia in 18.2% obese children; high BMI, cholesterol, triglycerides. Keywords: Dyslipidemia, Life style , Pediatric obesity, Prevalence